Metabolic regulation of interferon-mediated innate antiviral immunity - Zhong, Tian; Cao, Qi; Ma, Zhiyue; Jiang, Caiyu (Frontiers in Immunology, 2025)
Respiratory viral infections pose a major global public health challenge, with pathogens such as influenza viruses, novel coronaviruses, and respiratory syncytial virus exerting serious threats to human health. These infections often progress to severe disease in children, the elderly, and individuals with compromised immunity. Due to their anatomical exposure and relatively weak mucosal defenses, the upper respiratory tract—including the nasal cavity and throat—serves as a primary portal of entry for these pathogens. Such infections can lead to otolaryngological conditions such as anosmia and otitis media, and may further exacerbate illness in susceptible populations. After viral invasion, the host perceives pathogens through pattern recognition receptors (PRRs), rapidly activating the expression and signaling pathways of type I and type III interferons (IFN). This plays a core role in antiviral defense. Notably, viral infection profoundly reshapes the host cell’s metabolic network, involving widespread alterations in carbohydrate, lipid, amino acid, and nucleotide metabolism. During this process, key metabolic products are released or generated. These are the products of metabolic reprogramming and important immune regulatory molecules that can directly or indirectly modulate the host’s antiviral immune response, particularly the interferon pathway. These findings reveal that viral invasion, host metabolic reprogramming, and interferon-mediated antiviral immunity form a tightly intertwined, and dynamically interact a regulatory network of”virus-metabolism-IFN”. This profoundly elucidates the underlying regulatory logic of the metabolic microenvironment in antiviral immunity. Understanding this mechanism offers new perspectives for diagnosis and treatment: targeting metabolic nodes or utilizing metabolic modulators, as well as combined strategies with IFN, and may become novel approaches for the prevention and treatment of upper respiratory viral diseases. This review focuses on the core role of IFN-mediated innate immunity in viral defense and its interactive regulation with metabolic reprogramming. It reviews the progress of studies on how metabolic products regulate the IFN pathway and antiviral responses through various mechanisms, and explores the potential clinical application prospects of metabolic regulation in local immune defense and the prevention and treatment of viral infections.